Host–guest interaction of cucurbit[8]uril with oroxin A and its effect on the properties of oroxin A - Zeng, Zhishu; Xie, Jun; Luo, Guangyan; Tao, Zhu; Zhang, Qianjun (Beilstein Journal of Organic Chemistry, 2020)
In this study, we investigated the host–guest interactions between oroxin A (OA) and cucurbit[8]uril (Q[8]) using 1H NMR, MS, UV–vis and IR spectroscopy. The results showed that OA and Q[8] formed an inclusion compound (OA@Q[8]) with a molar ratio of 1:1 and a binding constant of 1.299 × 107 L·mol−1. In addition, the effect of Q[8] on the properties of OA was investigated through comparative experiments. The solubility of OA in water increased 22.47-fold when the concentration of Q[8] was 1 × 10−4 mol·L−1. Q[8] hardly affected the antioxidant capacity of OA, while the cumulative release of OA in gastric juice increased 2.3-fold after forming the inclusion compound with Q[8].
Keywords: cucurbit[8]uril; host–guest interaction; inclusion complex; oroxin A; properties